Resilience and social isolation in people living with HIV: a case study in Iran - Mehri Lotfalizadeh; Amirreza Sabzi; Jamileh Farokhzadian; Nazanin Tabebordbar (BMC Research Notes)
Abstract Objective People living with HIV (PLHIV) often face increased vulnerability due to factors like social isolation and reduced resilience. These factors can negatively impact health outcomes, quality of life, and well-being for both PLHIV and their families. Therefore, healthcare providers should carefully assess these variables when providing care for PLHIV. This study evaluated the levels of resilience and social isolation among PLHIV. Results PLHIV demonstrated high levels of resilience (77.16 ± 18.78) and moderate levels of social isolation (52.77 ± 6.63). Additionally, a strong inverse correlation was found between resilience and social isolation (r = -0.60, p < 0.001). Given the results, it is imperative for health policymakers, healthcare providers, and psychologists to prioritize strategies that enhance resilience and reduce social isolation among PLHIV.